Образ писателя в публицистике Ивана Бунина 1920 г. - Николаев, Дмитрий (Acta Polono-Ruthenica, 2019)
The image of the writer plays an important role in the publicist works of Ivan Bunin in 1920. It is the image of the author struggling against the Bolsheviks, and the image of those writers who helped the Bolsheviks propaganda as well as “new Soviet writers”. In 1920 Bunin as the most signif-icant writer of the Russian Diaspora focuses on the most famous writer among those who, according to Bunin, supports the Bolsheviks – Maxim Gorky. Bunin also pays close attention to the contro-versy with H.G. Wells: this is due to the role that the English writer played in the context of Soviet Russia. Bunin’s works in 1920 are written as a reaction of the Russian writer to the various texts published in the press, and the discussion with the works of his main opponents – Gorky and Wells.